2010
DOI: 10.4050/jahs.55.042002
|View full text |Cite
|
Sign up to set email alerts
|

Multiterrain Vertical Drop Tests of a Composite Fuselage Section

Abstract: A 5-ft-diameter composite fuselage section was retrofitted with four identical blocks of deployable honeycomb energy absorber and crash tested on two different surfaces: soft soil, and water. The drop tests were conducted at the 70-ft. drop tower at the Landing and Impact Research (LandIR) Facility of NASA Langley. Water drop tests were performed into a 15-ft-diameter pool of water that was approximately 42-in. deep. For the soft soil impact, a 15-ft-square container filled with fine-sifted, unpacked sand was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…On ground impact it is triggered to unfold into a block of honeycomb, which then crushes down to absorb crash energy, thus protecting the fuselage. The device has been retrofitted on an MD-500 helicopter and two full-scale crash tests were carried out with and without the DEA with velocity components 7.9 m/s (26 ft/s) vertical and 12.2 m/s (40 ft/s) horizontal [25]. It was found that the helicopter with the DEA showed no structural crash damage, whilst the baseline helicopter had damage to keel beams and subfloor structure as well as buckled and fractured seat frames.…”
Section: Use Of Composites In Crashworthy Subfloor Structuresmentioning
confidence: 99%
“…On ground impact it is triggered to unfold into a block of honeycomb, which then crushes down to absorb crash energy, thus protecting the fuselage. The device has been retrofitted on an MD-500 helicopter and two full-scale crash tests were carried out with and without the DEA with velocity components 7.9 m/s (26 ft/s) vertical and 12.2 m/s (40 ft/s) horizontal [25]. It was found that the helicopter with the DEA showed no structural crash damage, whilst the baseline helicopter had damage to keel beams and subfloor structure as well as buckled and fractured seat frames.…”
Section: Use Of Composites In Crashworthy Subfloor Structuresmentioning
confidence: 99%
“…This drop test was conducted to evaluate the energy attenuation capabilities of the deployable concept for water impact and to generate test data for correlation with analytic models. More details on this test are reported in the paper by Kellas et al (2008). A 15-ft-diameter pool, filled to a height of 42 inches, was located beneath the drop tower.…”
Section: Multi-terrain Impact Simulationmentioning
confidence: 99%
“…These results demonstrate the importance of mesh discretization studies when using the SPH method for simulating water impact. Soft Soil Impact As a final evaluation, the composite fuselage section retrofitted with four blocks of the DEA was impacted onto soft soil (sand) at 37.4-fps, as reported in Kellas et al (2008). A 15-ft x 15-ft wooden box was built and located beneath the drop tower.…”
Section: Multi-terrain Impact Simulationmentioning
confidence: 99%
“…The Italian Aerospace Research Centre recently conducted a drop test of a full-scale fuselage section of a regional aircraft made entirely of composite materials (Luigi et al, 2019). In addition to the drop tests of the fuselage section, the impact tests of the subfloor structures were also carried out to investigate energy absorption capacities and impact loading responses (Waimer et al, 2017;Sturm et al, 2014;Kellas and Jackson, 2010). These experiments have facilitated the development of various research topics aimed at improving crashworthiness of aircraft.…”
Section: Introductionmentioning
confidence: 99%